Fossil fuels, nuclear energy and renewable energy - Cavalcanti , Jessica Tamyris de Freitas; de Lima, Julia Guedes; Melo , Myrella Rayane do Nascimento; Monteiro, Eliana Cristina Barreto; Campos-Takaki , Galba Maria (Seven Editora, 2023)
For the generation of energy sources, natural resources are used by man. The rapid growth of human populations, related to the phenomena of globalization and industrialization, has significantly increased the increase in the consumption of world energy sources. These energy sources can be renewable when the resources used are inexhaustible due to their constant renewal in the environment and non-renewable due to their slow process of formation in nature, thus becoming finite. Climate change is caused by increased emissions of greenhouse gases, mainly CO2, coming mainly from the burning of fossil fuels. However, new energy sources have been sought as a way not only to diversify the energy matrix of countries around the globe but also to develop alternatives that seek a reduction of impacts, especially of an environmental nature. While renewable energy sources such as solar, wind, and wave energy can provide eco-friendly alternatives to fossil fuels and nuclear power, the intermittent nature of these energy sources requires an energy storage medium that allows for a continuous supply of energy. The work developed emphasizes that regardless of the type of generating source, whether renewable or non-renewable, there is no zero impact on the generation of energy. Knowledge of the low energy efficiency of renewable sources, investments, and the intermittency of schemes that is a characteristic of many of them, has shown that renewable energy sources will almost always be complementary to non-renewable ones.DOI:https://doi.org/10.56238/alookdevelopv1-146